Antioxidant Enzyme Expression in Clinical Isolates of Pseudomonas aeruginosa: Identification of an Atypical Form of Manganese Superoxide Dismutase - Britigan, Bradley E. (American Society for Microbiology, 2001)
Expression of superoxide dismutases (FeSOD and MnSOD) and catalases by laboratory strains of Pseudomonas aeruginosa is modulated by exogenous factors. Whether clinical isolates behave similarly and whether antioxidant enzyme expression influences P. aeruginosa virulence remain unclear. Fifty-seven P. aeruginosa blood culture isolates, plus seven pairs of blood and local-site isolates, were examined for FeSOD, MnSOD, and catalase production in vitro. Under iron-replete growth conditions FeSOD and catalase activities were maximized. MnSOD was not detected. FeSOD and catalase activity decreased under iron-limited growth conditions, whereas MnSOD activity appeared. SOD and catalase activity did not change with site of isolation or by patient. MnSOD could not be expressed by one isolate due to a missense mutation in sodA that produced a premature stop codon. Eleven percent of the isolates expressed a novel, rapidly migrating MnSOD that was associated with missense mutations in the normal stop codon of sodA. We conclude that clinical P. aeruginosa isolates vary little in FeSOD and catalase expression. Some strains produce a newly described MnSOD variant, whereas one is deficient in MnSOD production. The absence of MnSOD expression in a P. aeruginosa strain causing invasive human disease indicates that MnSOD is probably not essential for P. aeruginosa virulence.